Influence of Facesheet Thickness of Rubber Wood Honeycomb Composites on Flexural Properties - Yaakob, Mohd Yuhazri; Teng Teng, Jennise Tan; Sihombing, Haeryip; Abdullah, Abu; Akmal, Suriati (Journal of Advanced Research in Applied Mechanics, 2020)
Honeycomb sandwich composite is a well-known material that receives good responds in the industries due to its low density and excellent mechanical properties. The thickness of the facesheet is one of the highly concerned parameter in the sandwich composite. It is to introduce its optimal mechanical properties with ideal facesheet thickness in terms of layer, so that there is no unnecessary weight from the facesheet added to the composite structure. In this research, the honeycomb composite is fabricated for high strength applications via vacuum bagging. Samples of solid rubber wood without facesheet, open cell honeycomb core and closed cell honeycomb core are investigated. The thickness of the facesheet in terms of number of layers ranging from one to five layers in the sandwich structure is investigated under flexural test according to the ASTM standard. It is noticed that the composite with three or five layers of facesheet have exhibited excellent flexural properties.